Transparent and flexible antibacterial photocrosslinked thin films against the S. aureus and E. coli pathogen bacteria - BİRTANE, HATİCE; KAHRAMAN, MEMET VEZİR (ELSEVIER, 2021)
The study aims to obtain simple, transparent, and flexible coatings that are produced using an environmentally-friendly method, have either positive or negative charge density on their surfaces, and have antibacterial properties. For this purpose, poly(ethylene glycol) diacrylate (PEGDA), trimethylolpropane triacrylate (TMPTA), and trimethylolpropane tris(3-mercaptopropionate) (TMPTMP) were crosslinked using the thiol-ene click reaction in the presence of UV light. Ammonium salt is known to have antibacterial properties due to its positively charged surface and was added to the coating formulation to positively charge the surface of the glycidyl-trimethylammonium chloride (GTMAC) coating and negatively charge the sodium 3-mercapto-1-propanesulfonate (3-MPS) surface. The thiol-ene click reaction was used in the coatings that were prepared by using the base formulation and adding 3-MPS while the thiol-ene and thiol-epoxy click reactions were used together for the addition of GTMAC to the formulation. The structural characterization of the coatings was made using FTIR, the thermal behaviors of the coatings were determined using thermogravimetric analysis (TGA), and the morphologies and chemical compositions of the coatings were examined using SEM and SEM-EDAX images. The antibacterial activities of the coatings were tested using the inhibition zone method against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria that have different cell wall properties and can serve as models for similar bacteria.
Keywords: GTMAC; Antibacterial coating; Thiol-ene dick reaction; Photocurable coating; SILVER NANOPARTICLES; COATINGS; ACID